380 kV Superconducting Fault Current Limiter Feasibility Study - Noe, Mathias (Karlsruher Schriftenreihe zur Supraleitung, 2023)
In this study the technical and economic feasibility of a 380 kV, 5 kA resistive type superconducting fault current limiter was investigated. Conceptual designs were developed with superconducting tapes cooled by liquid nitrogen and arranged in bifilar coils. A cryostat was designed using FEM simulations taking into account the non-linear voltage distribution. For the complete system including current limiting reactors and cooling system, the investment and operation costs were calculated.